2018
DOI: 10.1182/blood-2018-99-118876
|View full text |Cite
|
Sign up to set email alerts
|

Validation and Feasibility of a Point of Care Screening Test for Sickle Cell Disease in a Resource Constrained Setting — a New Frontier

Abstract: Introduction and Objectives Sickle cell disease (SCD) is a neglected tropical disease disproportionally affecting malaria endemic regions of sub-Saharan Africa. Estimated to affect up to 3% of the population in some areas, 50-90% of children affected with SCD die before age five due to lack of diagnosis and preventative care. Early screening and intervention improves survival, but is not the standard of care throughout much of the continent. Kenya, like several other sub-Saharan African countrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Hemoglobinopathy screening studies conducted in low-resource settings, using centralized laboratories, have reported that up to 50% of test results never reach to the patients due to infrastructural challenges. [52][53][54] In resource-rich countries, standard clinical laboratory tests (high-performance liquid chromatography (HPLC) or hemoglobin electrophoresis are typically used in the diagnosis of hemoglobin disorders. 33 Additionally, genetic testing, usually polymerase chain reaction-based, can be used to precisely identify globin gene mutations.…”
Section: Introductionmentioning
confidence: 99%
“…Hemoglobinopathy screening studies conducted in low-resource settings, using centralized laboratories, have reported that up to 50% of test results never reach to the patients due to infrastructural challenges. [52][53][54] In resource-rich countries, standard clinical laboratory tests (high-performance liquid chromatography (HPLC) or hemoglobin electrophoresis are typically used in the diagnosis of hemoglobin disorders. 33 Additionally, genetic testing, usually polymerase chain reaction-based, can be used to precisely identify globin gene mutations.…”
Section: Introductionmentioning
confidence: 99%
“…Homa Bay county is yet to implement newborn screening for sickle cell disease. This is despite the high prevalence of sickle cell disease among infants who were accessing maternal and child health services in the county, which was found to be at 9.6% (Wanjiku et al, 2018). Routine newborn screening for sickle cell disease is recommended in regions where sickle cell disease prevalence at birth is 0.05% or more (DeBaun & Galadanci, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Homa Bay county is yet to implement NBS for SCD. This is despite the high prevalence of SCD among infants who were accessing MCH services in the county, which was found to be at 9.2% (Wanjiku et al, 2018).Routine NBS for SCD is recommended in regions where SCD prevalence at birth is 0.05% or more (DeBaun & Galadanci, 2022). Further, no prior study, to the best of my knowledge, had been conducted in the county to assess the acceptability of such potentially bene cial program.…”
Section: Introductionmentioning
confidence: 99%